2001
DOI: 10.1046/j.1365-2648.2001.01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and psychosocial factors in persons living with HIV

Abstract: Aim of the study-This pilot study was designed to examine the relationships among spirituality and psychosocial factors in a sample of 52 adult males living with human immunodeficiency virus (HIV) disease and to determine the most reliable spirituality measure for a proposed longitudinal study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 46 publications
(65 reference statements)
11
110
1
1
Order By: Relevance
“…These results are in line with research with populations with other health conditions such as human immunodeficiency virus or Alzheimer disease or healthy populations. [120][121][122][123][124][125][126][127][128][129] Spirituality can be an important component in psychotherapy. [130][131][132] Beneficial effects of meaning making interventions on SE, optimism and self-esteem are reported.…”
Section: Psychological Resources In Sci C Peter Et Almentioning
confidence: 99%
“…These results are in line with research with populations with other health conditions such as human immunodeficiency virus or Alzheimer disease or healthy populations. [120][121][122][123][124][125][126][127][128][129] Spirituality can be an important component in psychotherapy. [130][131][132] Beneficial effects of meaning making interventions on SE, optimism and self-esteem are reported.…”
Section: Psychological Resources In Sci C Peter Et Almentioning
confidence: 99%
“…Subscale scores are derived for religious well-being and existential well-being. The scale has been found to be psychometrically sound with persons with HIV infection (Carson & Green, 1992;Carson, Soeken, & Belcher, 1991;Tuck, McCain, & Elswick, 2001). The SWBS mean (standard deviation) was 88.94 (21.34) for this sample.…”
Section: Impact Of Event Scale (Ies; Horowitz Et Al 1979)mentioning
confidence: 99%
“…This finding suggests that influences on self-management of chronic illness among diverse groups of people may be understood from a sociocultural context. Tuck et al (2001) indicated that spirituality, as measured by the existential well-being subscale of the Spiritual Well-being Scale, was positively related to effective coping strategies and enhanced quality of life among persons living with Human Immunodeficiency Virus (HIV). In another study, Meisenhelder and Chandler (2002) examined the frequency of prayers and the importance of faith and health status among older Native Americans.…”
Section: Introductionmentioning
confidence: 99%